Metaphor and Conceptual Research in the Poetry of O'roz Haydar: Analysis of the Poem "Days of the Past" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the analysis of metaphorical devices and conceptual research in the poetry of Oroz Haydar. Using the example of the poet's poem "Byghan kunlar", we will consider how he conducts deep spiritual and ontological research through simple words, as well as how he artistically expresses the themes of injustice, loneliness and timelessness described in the poem using metaphors. The article attempts to shed light on the main metaphors in the poem, their semantic and aesthetic properties, and their role in interpreting social and spiritual problems.